The influence of the surface microtexture on wettability properties and drop evaporation; Surface and Coatings Technology; Vol. 375 - Misyura S. Ya. Sergey Yakovlevich; Kuznetsov G. V. Geny Vladimirovich; Feoktistov D. V. Dmitriy Vladimirovich; Volkov R. S. Roman Sergeevich; Morozov V. S. Vladimir Sergeevich; Orlova E. G. Evgeniya Georgievna (2019, 2019)
Title screen